2018
DOI: 10.1186/s40463-018-0316-5
|View full text |Cite
|
Sign up to set email alerts
|

Long term follow-up demonstrating stability and patient satisfaction of minimally invasive punch technique for percutaneous bone anchored hearing devices

Abstract: ObjectiveMinimally Invasive Ponto Surgery (MIPS) was recently described to facilitate the placement of percutaneous bone anchored hearing devices. As early adopters of this new procedure, we sought to perform a quality assurance project using our own small prospective cohort to justify this change in practice. We chose to examine device stability and to gauge our patients’ perspective of the surgery and their overall satisfaction with the process.MethodsA total of 12 adult patients who underwent MIPS between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 16 publications
3
17
0
Order By: Relevance
“…None of these studies used a cannular as part of the procedure. Published results of MIPS without a control group report either no loss Sardiwalla et al or a 96% (74/77) survival rate with 2 losses at 2 and 8 weeks, respectively occurring without any evidence of inflammation. These were attributed to incorrect drilling technique and CSF leak, respectively, Johansson et al The only study comparing MIPS with an open soft tissue‐preserving technique demonstrated a 12.1% loss rate in the MIPS group compared with a 3.3% loss rate in the other at 12 weeks, Calon et al All their losses occurred between 25 and 90 days with possible causes of angulated or incomplete insertion and overheating mentioned in the discussion.…”
Section: Discussionmentioning
confidence: 95%
“…None of these studies used a cannular as part of the procedure. Published results of MIPS without a control group report either no loss Sardiwalla et al or a 96% (74/77) survival rate with 2 losses at 2 and 8 weeks, respectively occurring without any evidence of inflammation. These were attributed to incorrect drilling technique and CSF leak, respectively, Johansson et al The only study comparing MIPS with an open soft tissue‐preserving technique demonstrated a 12.1% loss rate in the MIPS group compared with a 3.3% loss rate in the other at 12 weeks, Calon et al All their losses occurred between 25 and 90 days with possible causes of angulated or incomplete insertion and overheating mentioned in the discussion.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, implant extrusion was mentioned several times as a warrant for further research ( 29 33 , 35 , 39 ). Also, there were limited long-term results with only one small cohort study ( 36 ). Moreover, a standardized procedure was lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, a nonsignificant increase in implant extrusion rate was found when using the MIPS technique ( 35 ). Besides these encouraging short-term results, however, there is only one small prospective cohort study of Sardiwalla et al ( 36 ) with a longer follow-up (minimal 12 months). This study concluded device stability and patient satisfaction with the MIPS procedure ( 36 ).…”
Section: Introductionmentioning
confidence: 98%
“…Examples include studies looking at surgical outcomes, studies investigating patient satisfaction outcomes, and studies examining quality indicators. [17][18][19][20][21][22] Residency/ education-specific PS/QI was previously examined in depth by our research team 5 ; major focus areas include use of simulation for risk-free surgical training [23][24][25] and development of methodologies for evaluating surgical competency. [26][27][28] The greatest areas of research need identified in this OHNS dedicate PS/QI systematic review were: 1) examination of the existence and impact of multidisciplinary care, and 2) investigation of healthcare disparities.…”
Section: Discussionmentioning
confidence: 99%